Normalisasi Hubungan Arab Saudi - Iran dalam Mendukung Saudi Vision 2030 - Auseve Banartya, Incha; Tamsyah, Indra (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2025)
This research analyses the impact of the diplomatic normalization between Saudi Arabia and Iran on the sustainability of Saudi Vision 2030. Utilizing Complex Interdependence Theory, this study examines how the changing dynamics of the relationship between these two nations influence the main pillars of Saudi Vision 2030’s transformative vision, encompassing a thriving economy, a prosperous nation, and a vibrant society. This is viewed through economic, energy, political-security, and socio-cultural aspects. The findings indicate that the normalization of relations, mediated by China in March 2023, was driven by a mutual awareness that the costs of conflict and regional instability far outweighed the potential gains from competition. This normalization significantly supports Saudi Vision 2030. Its positive impacts include increased FDI and non-oil economic diversification opportunities, global oil market stabilization and potential renewable energy cooperation, proxy conflict reduction and an enhanced Saudi position in international organizations, as well as increased social mobility and tourism. Although challenges such as sanctions on Iran and fragile trust persist, this normalization represents an essential pragmatic step towards regional stability and Saudi Arabia’s transformative ambitions.